The Implementing ISO 9001 In Manufacture Industry - Wella Wella; Laurentia Chia (Universitas Multimedia Nusantara, 2019)
In 2015 ISO 9001 significantly reviewed and new requirements for certification were introduced. One of the new requirements is risk-based thinking. The risk-based thinking has to be addressed and managed in all aspects of quality management system processes and functions. In ISO 9001:2015 an organization required to take into those risk linked to quality and customer satisfaction. Risk management can be a guideline for the implementation of ISO 9001:2015. This research is only focused on information technology department at PT Softex Indonesia. The methodology of this implementation applies the seventh clause of ISO 9001:2015. Measurements performed by using maturity model and seventh audit stage. After the implementation, the organization needs to maintain the requirements of ISO 9001:2015 and try to continuously improve its quality performance.